PFA-100 monitoring of von Willebrand factor (VWF) responses to desmopressin (DDAVP) and factor VIII/VWF concentrate substitution in von Willebrand disease type 1 and 2 - van Vliet, Huub H. D. M.; Kappers-Klunne, Mies C.; Leebeek, Frank W. G.; Michiels, Jan J. (Thrombosis and Haemostasis, 2008)
Dose-response relationship was studied between PFA-100 closure times (PFA CTs) and factor (F)VIII-von Willebrand factor (VWF) parameters in patients with von Willebrand disease (VWD) type 1 and type 2 before and after treatment with DDAVP (n=84) or FVIII/VWF concentrate (n=38). DDAVP treatment of patients with VWD type 1 normalised the PFA CTs by increasing VWF levels to normal. Of the 14 patients with VWD type 2, PFA CTs did not normalize in eight. Haemate-P substitution in patients with VWD type 1 induced a less favourable response as compared to DDAVP, because PFA CTs did not correct in all patients. Of 12 patients with VWD type 2 treated with Haemate-P, six showed a correction of PFA CTs (<250 sec), which correlated with the normalisation of the VWF CB/ Ag ratio. In-vitro studies were performed by using whole blood of patients with VWD and adding various amounts of FVIII/VWF concentrate. Addition of Haemate-P induced an increase of the VWF CB/Ag ratio from 0.30 to 0.70 in blood of patients with VWD type 2 with correction of the PFA CTs. Immunate did not result in an increase of VWF CB/Ag ratio in blood of VWD type 2 patients, and the PFA CTs remained prolonged. We conclude that PFA-100 might be an adequate instrument not only for diagnosis but also for monitoring of DDAVP responses and FVIII/ VWF substitution of patients with VWD type 1 and 2,but this is dependent upon the type of VWD and the concentrate used.
Keywords: von Willebrand disease; DDAVP; Haemate-P; PFA-100; vonWille-brand factor collagen binding